EFEKTIVITAS BIMBINGAN KELOMPOK DENGAN TEKNIK SELF MANAGEMENT UNTUK MENINGKATKAN KONTROL DIRI SISWA KELAS X SMK KARYA PERJUANGAN CIPONGKOR - Siti Nurul Inayah; Siti Fatimah; Ardian Renata Manuardi (IKIP Siliwangi, 2026)
This study addresses the issue of low self-control observed among students. The objective of this research is to assess the effectiveness of group counseling services using Self Management techniques in improving students' self-control. The research employs a Mixed Method approach, chosen for its suitability to address research questions that involve both outcomes and processes, incorporating both quantitative and qualitative data. The study utilizes an explanatory sequential design with a pretest-posttest approach. Purposive sampling was used to select the sample, which comprised students from class X at SMK Karya Perjuangan Cipongkor, based on specific characteristics. The results indicate that group counseling services using self-management techniques are effective in enhancing the self-control of students in class X at SMK Karya Perjuangan Cipongkor with a population size of 40 individuals and a sample of 8 individuals.. The average score difference between the posttest and pretest was 12.287848, with a t-value of -10.560 and a significance value of 0.000. The significance value of 0.000, which is less than 0.05 at a 95% confidence level, confirms the effectiveness of the intervention